Green HRM and Environmental Performance; the Role of Green Transformational Leadership and Green Innovation - Hasan Raza; Farwa Shah; Maria Masood; Maryam Bibi (Research Journal of Psychology, 2025)
This study investigates the impact of Green Human Resource Management (GHRM) on Environmental Performance (EP) in small and medium-sized enterprises (SMEs), with Green Innovation (GI) as a mediating variable and Green Transformational Leadership (GTFL) as a moderator. Rooted in the Resource-Based View (RBV) and Ability-Motivation-Opportunity (AMO) theory, the research aims to explore how internal organizational capabilities, specifically HRM practices and leadership, contribute to sustainability through innovation. Although large firms have dominated the sustainability discourse, this study redirects attention toward SMEs, which often lack formalized systems but hold significant environmental impact potential. A quantitative, cross-sectional research design was employed using structured questionnaires administered to 530 managers and employees across SMEs in Pakistan. After data screening, 290 valid responses were analyzed using Structural Equation Modeling (SEM). Measurement reliability was confirmed through Cronbach’s alpha and composite reliability, while validity was established via AVE and discriminant validity metrics. Hypotheses were tested to examine both direct and moderated relationships. The findings reveal that GHRM significantly enhances EP and that GI partially mediates this relationship. GTFL significantly moderates the effect of GHRM on GI, indicating that leadership enhances the translation of HR practices into innovative green outcomes. However, GTFL does not significantly moderate the direct relationship between GHRM and EP or between GI and EP, suggesting that its influence is more salient in fostering innovation rather than directly affecting environmental outcomes. The study contributes to the sustainability literature by elucidating the pathways through which GHRM affects EP, emphasizing the critical roles of innovation and leadership. Implications are offered for SME managers and policymakers seeking to embed environmental strategies within organizational systems.